(untitled) (LACCEI, 2024)
The present project was conducted in order to evaluate whether students meet certain criteria that employers use most frequently in their recruitment processes on the LinkedIn professional platform. Using the Iceberg model proposed by Spencer Spencer (1993) and the Competency Model of Martha Alles (2006), students of the Escuela Superior Politécnica del Litoral who are studying Integrating Subject in the II PAO 2022, a period that corresponds from September 26, 2022, to February 17, 2023, are evaluated, applying observation guide through the review of profiles on LinkedIn allowing to identify strengths and weaknesses before the recruitment processes. This study also evaluates the profiles of the main ESPOL employers to identify the criteria expected to be evidenced by the student in the process of graduation in their LinkedIn profile. Subsequently, the information obtained was coded by authorized ESPOL personnel and finally, the results were obtained. One of the main ones is that thirty-four percent of graduating students do not have a LinkedIn profile. One of the faculties with the highest participation in the platform is the Faculty of Natural Sciences and Mathematics.